Administrative and Legal Status of the National Police of Ukraine as a Subject of State Policy Implementation in Human Rights and Freedoms (Law and Safety, 2020)
The article is focused on studying the phenomenon of the administrative and legal status of the National Police as a subject of Ukrainian state policy implementation in human rights and freedoms. The author outlines the essence and content of the administrative and legal status of the National Police of Ukraine through the leading categories of "law" and "freedom", which are important for the democratic processes developing in Ukrainian society.The administrative and legal status of the National Police of Ukraine is considered as a set of characteristics and powers entrusted in the state legislation, a set of the following components: target – determined by the mission of the police to promote the state policy implementation in the fight against crime and peacekeeping, enforcement of rights, public and state interests; organizational – characterizes the structure of the National Police, consisting of a central police control facility, which consists of organizationally integrated structural units that ensure the implementation of the police tasks in human rights protection; competent – related to the definition of tasks, functions, rights, and duties, as well as the degree of responsibility of the law enforcement and its units and employees, determining the focus of their activities on the protection of the individual and the guarantee of the legitimacy of counteracting the state on the part of the person to protect their rights and freedoms.In practice, the implementation of the new administrative and legal status enables law enforcement to approve the law, enhance the communication and legal culture of police officers, overcome the traditional politicization and militarization of law enforcement by updating the organizing strategies of human rights activities, strengthen the state and professional discipline, make the police activities transparent, improve the control system and responsibility of police structures and professionals for malpractice.
Keywords: National Police; administrative and legal status; rights; human freedoms; state and community; legal system of Ukraine